1987
DOI: 10.1128/mcb.7.2.898
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the rat platelet factor 4 gene: a marker for megakaryocyte differentiation.

Abstract: A rat platelet factor 4 (PF4) cDNA has been isolated by immunoscreening a gXl 1 rat megakaryocyte cDNA expression library. Sequence analysis of the rat PF4 cPNA revealed that this megakaryocyte protein is composed of a leader sequence of 29 amino acid residues and a mature protein sequence of 76 amino acid residues. The structure of rat PF4 derived from its cDNA shows a marked homology with the amino acid sequence of human PF4 obtained by classical protein chemistry techniques. This observation is particularlv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 48 publications
3
44
0
Order By: Relevance
“…This fourth exon of the IP-10 gene almost exclusively encodes this 3' untranslated region and may play a role in the inducible transient expression of the IP-10 mRNA. In contrast, both rat (11) and human (28) PF4 genes contain short 3' untranslated regions and are constitutively expressed in platelets. This is consistent with the hypothesis that the 3' untranslated region of the IP-10 gene is responsible, at least in part, for its regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fourth exon of the IP-10 gene almost exclusively encodes this 3' untranslated region and may play a role in the inducible transient expression of the IP-10 mRNA. In contrast, both rat (11) and human (28) PF4 genes contain short 3' untranslated regions and are constitutively expressed in platelets. This is consistent with the hypothesis that the 3' untranslated region of the IP-10 gene is responsible, at least in part, for its regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the genomic organization of a member of this family of homologous cytokines, PF4, has been determined from the rat genome (11). A comparison of the rat PF4 cDNA sequence with its genomic sequence has revealed that the PF4 gene is organized into three exons and two introns.…”
Section: *Corresponding Authormentioning
confidence: 99%
“…Experiments to determine the arrangement of LD78 genes on human chromosomes are in progress in our laboratory. Genomic organizations of several other members of the new cytokine superfamily have recently been determined (6,13,15,18,22,28,36), and their structures are schematically summarized in Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet factor 4 (PF4) is expressed exclusively in megakaryocytes and platelets. 1 Because the PF4 gene is activated during the late stages of megakaryocytopoiesis, it is useful as a specific marker of megakaryocytic differentiation. 2 We have previously sequenced and characterized the rat PF4 promoter.…”
Section: Introductionmentioning
confidence: 99%